Research on Linux network packet buffer recycling toward multi-core processor - YAO Qi; LIU Ji-qiang; HAN Zhen; SHEN Chang-xiang (Tongxin xuebao)
A lock-free algorithm for Linux packet buffer recycling on multi-core processor was proposed.Through making a model of Linux network packet forwarding, the principle of Linux packet buffer recycling was analyzed, and the main reason that the mechanism wasn’t extensible on multi-core processor was pointed out .It was that mutual exclusion and cache coherence operations consumed too much CPU clock tick.A new buffer recycling algorithm named MSRQ was designed and implemented.With the new algorithm, the parallel operations on the recycling queue were permitted without mutual exclusion on multi-core processor.And the new algorithm had better cache behavior than original recy-cling algorithm.The experiment result shows that the performance of Linux network packet forwarding with the new algorithm can be improved more than 67%.